Mason Brayman, Revised Statutes of the State of Illinois 176 (1845) - (:unkn) unknown (My University, 1845)
Criminal Jurisprudence, § 139: Prohibited the carrying of "any pistol, gun, knife, dirk, bludgeon or other offensive weapon, with intent to assault any person. Punishable by fine up to $100 or imprisonment up to 3 months.
Keywords: CARRY - INTENT TO COMMIT CRIME